A medication self-management system with real-time health monitoring - Lakshmi Joshitha, K; Suresh, Aadhira; Bharathi, B; E. Dhivya, G (International Journal of Engineering and Technology, 2018)
India is the world's second largest country with lots of human resource. According to a survey of United Nations Department of Economic and Social Affairs, Population Division, with a tremendous medication and monitoring facilities in the health care, the rise in the elderly population will be from 7.5% in 2010 to 11.1% in 2025.However half of the elderly population are dependent and experience greater burden of ailments like the cardiovascular and circulatory illness, arthritis etc. With most of the youngsters working, the issue in taking care of the elderly people needs to be automated in all dimensions. The proposed work aims at designing a wearable device for health monitoring of elderly people who are not in a position to move swiftly. The device monitors the userâ€™s ECG and pulse rate. The device is compact and user friendly. Besides, the proposed system also includes an automated pill box which issues the right pill on command that is loaded al-ready in it.The sensed data is intimated through an android application to the concerned person. On reception, the data is analyzed and the person sends an appropriate code using a telegram application. This code activates the pill box to open up the right compartment and delivers the pill to the ailing elderly patient. Further monitoring can be done after the medication to ensure the patient's condition. The set up can as well be fitted in a wheel chair for the timely delivery of the pills to a person moving in it.Â Â
Keywords: Health Monitoring; Wearable Device; User Friendly; Automated Pill Box; Android Application.